Innovation in Facilities and Infrastructure Management to Improve Educational Quality at SDIT Nur Hidayah Surakarta - Muhammad Zainudin; Mudofir; Imam Makruf (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2026)
The management of educational facilities and infrastructure plays a strategic role in supporting the effectiveness of the learning process and improving the quality of education, particularly in Islamic educational institutions. Technological developments and the demands of 21st-century learning encourage educational institutions to innovate in managing educational facilities to make them more adaptive, efficient, and relevant to students’ needs. This study aims to describe the concept of educational facilities and infrastructure management, its functions, the principles of innovation from the perspective of Islamic education, and its implementation at SD IT Nur Hidayah Surakarta. The method used in this study was field research with a qualitative approach. Data were collected through observations, interviews, and documentation related to the management and innovation of school facilities and infrastructure. The findings show that facilities and infrastructure management includes the functions of planning, procurement, inventory, maintenance, and asset disposal, all of which must be carried out systematically, effectively, and accountably. Innovations in the management of Islamic educational facilities and infrastructure should be based on the principles of Islamic value integration, effectiveness and efficiency, accountability, and sustainability. The implementation of innovation at SD IT Nur Hidayah Surakarta is reflected through the use of digital learning media, the development of conducive classrooms, the optimization of laboratories, digital libraries, technology-based administrative systems, and the provision of educational playgrounds. These innovations have proven to improve learning quality, learning comfort, student engagement, and the effectiveness of educational services.